PENGARUH PEMBERIAN TEPUNG JAHE DAN TEPUNG KUNYIT PADA RANSUM TERHADAP KUALITAS EKSTERNAL TELUR PUYUH - Nugraha, Prayoga; Nur, Hanafi; Anggraeni, Anggraeni (Jurnal Peternakan Nusantara, 2018)
This research aims to improve the external quality of quail eggs both in terms of eggs full weight, eggs index, and eggshell thickness. This research also provides information of the effect of the treatment that has been tested on the external quality of quail eggs. Quail used is layer quailstrain Coturnix coturnix japonica produced by CV. Slamet Quail Farm as many as 225 quails. The feed used is commercial feed with trade mark SP2 produced by PT. Sinta Feedmill and the experimental layout used was Complete Random Layout (RAL) with the following treatment is: P0 (commercial feed without the addition of ginger flour and turmeric flour), P1 (Provision of commercial feed with addition of 1% ginger flour), P2 (provision of commercial feed with addition of 1% turmeric flour), and P3 (Provision of commercial feed with 0.5% addition of ginger flour and 0.5% turmeric flour). Treatment was performed on quail aged 35 days until age 80 days. Feed and drinking are givenin an adlibitum way (always available).Keywords: ginger flour, turmeric flour, the external quality of egg, commercial feed..